Broken debris of the temple assembled on the south face of the adhisthana - Temples of India Project Team (Jio Institute, 2024)
Broken debris from the original temple assembled on the south face of the adhisthana. Relief carvings of geometric, flora and fauna motifs feature all around the adhisthana.